Evaluasi Minat Bidang Usaha Investasi Penanaman Modal Asing (PMA) dan Penanaman Modal Dalam Negeri (PMDN) Provinsi Jawa Timur - Soegiri, Hary; Sukesi, . (Kajian Manajemen dan Bisnis, 2010)
The interest accrued.from cap.ital invested by investors in East Java is bigger compared to other areas in Indonesia. According to our research, several reasons exist that make investors choose East Java as their preferred investment destination. One of which is the availability of infrastructure projects that are of international standards and other supporting facilities such as ports, industrial zones, and airports as well as the integrated one-stop service in terms of acquiring licenses for investment.